Clinical Evaluation of Maxillary Arch Complete Denture Impressions Made by Undergraduate Students in a Dental College - Sharma, Rinu; Bhochhibhoya, A.; Acharya, B; Rana, SB; Sagtani, RA (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: An accurate impression is the foundation of denture fabrication process thus a practitioner should be aware of the possibility of including errors during this procedure. Time spent in making a good impression will reduce the time required in adjusting the final prosthesis as well as make it more comfortable for the patient in accepting the prosthesis.Materials and Methods: Maxillary arch final impressions made by undergraduate dental students on 106 edentulous patients were evaluated. The impressions were assessed on the basis of criteria’s like errors on mixing, flow, tray positioning, presence of voids, creases/irregularities, exposure of tissue stops and extension at posterior border. The data’s collected were analyzed for the frequency of occurrence and distribution of each type of errors.Results: It was found that 97.2% of students performed at least one detectable error during making of maxillary arch final impression. The number of errors made by students ranged from single to as much as seven errors in one impression. The most common error was lack of exposure of all tissue stops followed by presence of voids and creases/irregularities on impression surface.Conclusion: There is high possibility of including errors while making maxillary arch final impression by undergraduate dental students. The study highlights the need to explore novel techniques of clinical demonstrations and teaching important concepts to learning students. The inclusion of more pre-clinical exercises in undergraduate curriculum relating to manipulation of dental materials may improve skills of students in making accurate edentulous impressions.